Endrew and FAPE: Concepts and Implications for All Students With Disabilities. Issue 1 (January 2021) - Kauffman, James M.; Wiley, Andrew L.; Travers, Jason C.; Badar, Jeanmarie; Anastasiou, Dimitris
The opinion of the Supreme Court of the United States in the Endrew case has implications for the education of all students with disabilities. Implications for several categories of disability are discussed: those with autism spectrum disorder and those with disabilities often considered high incidence, particularly those placed for a significant portion of their school day in general education. The aspects of the Individuals with Disabilities Education Act most relevant to the Endrew case are also compared with Article 24 of the United Nations's Convention on the Rights of Persons with Disabilities. The opinion in Endrew may affect the course of special education and the role of behavior modification in meeting the needs of all students with disabilities.